User Satisfaction Management Information System Hospitals in Kuala Pembuang Regional General Hospital - Lasinrang Lasinrang; Rosihan Adhani; Muhammad Abdan Shadiqi; Syamsul Arifin; Mohammad Bakhriansyah (Lambung Mangkurat, 2024)
A computer-based Management Information System for hospitals is very important. Data was obtained that there were 89 hospitals (3%) that reported already having SIMRS but not running functionally, 294 hospitals (10%) did not have SIMRS, and 365 hospitals (12%) did not report SIMRS. Most of the employees are 20 – 35 years old. The purpose of this study is to determine the relationship between the age of the hospital management information system, the quality of the information, the quality of the system, and the quality of services provided to patients at Kuala Pembuang Hospital. This study uses cross-sectional design and observational analytical methods. For the sampling technique used the type probability sampling with 89 participants. Chi-square analysis results showed the value of age p values (p= 0.587), system quality (p= 0.000), information quality (p= 0.000) and service quality (p= 0.000). The results of multivariate analysis with logistic regression showed the p and ExpB values of the information quality variable (p=0.000, Exp B=10.267). There is a substantial relationship between user satisfaction with system quality, information quality, and service quality. In addition, there is no significant relationship between age and user satisfaction of the hospital management information system at Kuala Pembuang Hospital.